Fostering creativity and cultural bonds: revitalizing kasab crafts through arts education and community engagement in West Aceh, Indonesia - Lindawati, Lindawati; Naam, Muh Fakhrihun; Ismawan, Ismawan; Supadmi, Tri (Institut Seni Indonesia Surakarta, 2023)
This study aims to examine the school's efforts in introducing and preserving Kasab in West Aceh through art education and community collaboration. Kasab is gold thread embroidery on velvet cloth which is widely used in Acehnese weddings as a cultural product. Kasab was introduced to art education at the West Aceh High School through arts and culture subjects. This study used a qualitative approach. The research was conducted in five high schools in West Aceh District, Indonesia. Data collection techniques were carried out through interviews with students, teachers who teach arts and culture, and Kasab craftsmen. In addition, observations were also conducted to observe the collaborative learning process of the community and teachers, as well as literature studies on community collaboration and art education in the field of crafts. The results of the study show that collaborative art education in schools and communities regarding the introduction and process of making Kasab crafts is taught in the fine arts course, which begins with making decorative motifs. Next, the Kasab crafts were embroidered with gold thread. Students and teachers performed field studies at the Kasab craftsmen's place to observe the process of making Kasab. Later on, the students practice making Kasab at school, guided by the teacher and Kasab craftsmen. This activity is very important to be performed in every high school as an effort to preserve the Kasab craft in the West Aceh district.